1994
DOI: 10.1021/ac00082a025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glucose Oxidase-Modified Poly(phenylenediamine)-Coated Electrodes in vitro and in vivo: Homogeneous Interference by Ascorbic Acid in Hydrogen Peroxide Detection

Abstract: The response of glucose oxidase (GOx) modified poly(& phenylenediamine) coated P t disk electrodes to glucose was well-behaved with a rapid response time and displaying Michaelis-Menten kinetics. However, the glucose response was lowered in a concentration-dependent manner by ascorbic acid when the glucose calibrations were carried out in solutions containing this reducing agent. The possibility of a homogeneous redox reaction in which the H202 generated by the enzymatic oxidation of glucose at the GOx/polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
155
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(167 citation statements)
references
References 63 publications
9
155
3
Order By: Relevance
“…Pt/ PPD/GOx disk electrodes were prepared from Tefloncoated platinum/iridium (Pt/Ir 90%/10%) wire (125 vm bare diameter, 160 vm coated diameter (5T), Advent Research Materials, Suffolk, UK) following a previously reported procedure (Lowry et al, 1994a). Pt/ PPD/GOx cylinder electrodes were made from 5 cm lengths of the same 5T wire.…”
Section: Working Electrode Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…Pt/ PPD/GOx disk electrodes were prepared from Tefloncoated platinum/iridium (Pt/Ir 90%/10%) wire (125 vm bare diameter, 160 vm coated diameter (5T), Advent Research Materials, Suffolk, UK) following a previously reported procedure (Lowry et al, 1994a). Pt/ PPD/GOx cylinder electrodes were made from 5 cm lengths of the same 5T wire.…”
Section: Working Electrode Preparationmentioning
confidence: 99%
“…In order to ensure good GOx adsorption the exposed 4 mm of wire was then scored repeatedly with a scalpel blade. GOx was immobilised in PPD by potentiostatic electropolymenzation of the o-phenylenediamine monomer (o-PD, 300 mM) following a modified form of a previously reported procedure (Lowry et al, 1994a). Briefly, a deoxygenated solution of the monomer was prepared in PBS, pH 7.4.…”
Section: Working Electrode Preparationmentioning
confidence: 99%
See 3 more Smart Citations